Hyperbole or Reality? Investor Response to Extreme Language in Earnings Conference Calls - Bochkay, Khrystyna; Hales, Jeffrey; Chava, Sudheer (The Accounting Review, 2020)
ABSTRACT We develop a dictionary of linguistic extremity in earnings conference calls, a setting where managers have considerable latitude in the language they use, to study the role of extreme language in corporate reporting. Controlling for tone (positive versus negative) of language, we document that when managers use more extreme words in earnings conference calls, trading volume around the call increases and stock prices react more strongly. In addition, both effects are more pronounced for firms with weaker information environments. Linguistic extremity also affects analyst opinions and contains information about a firm's future operating performance. As such, our results provide evidence that markets are influenced not just by what managers say, but also how they say it, with extreme language playing an important role in communicating reality and not merely reflecting hyperbole.